Clinical effectiveness of customised sport shoe orthoses for overuse injuries in runners: a randomised controlled study - Hirschmüller, A; Baur, H.; Müller, S.; Helwig, P.; Dickhut, H. H.; Mayer, F. (British Journal of Sports Medicine, 2011)
Background and objectives: Treatment of chronic running-related overuse injuries by orthopaedic shoe orthoses is very common but not evidence-based to date.